Does Nutrition Really Matter for the Productivity of Smallholder Farmers? - Azra, Tilai; Rayenda Khresna, Brahmana; Hui, Wei You (Universiti Putra Malaysia Press, 2021)
Household-level data from Malaysia Smallholder paddy farmers are used to test whether higher caloric intake enhances family farm labour productivity. This study contests the notion behind the efficiency wages hypothesis. Farmers’ productivity is estimated using Data Envelopment Analysis. To avoid estimation bias from reverse causality, we utilize a two-stage least square approach by choosing prices, household demography, and farm assets as instrumental variables. The results show that high caloric intake significantly affects farmers’ productivity in a non-linear relationship. Farmers with obesity and overweight conditions produce less per unit of inputs and supply more labour than farmers with normal BMI and normal weight. The model results show that production inefficiency increases significantly with the high consumption calories, high BMI, and obesity of farmers providing solid support for the nutrition productivity hypothesis. The marginal effect on productivity falls drastically as caloric intake increases. These outcomes recommend that investing in the health sector in rural areas will improve farmer productivity. Policymakers should develop approaches that will maximize agricultural investments’ contribution to agricultural productivity and the overall rural economy.